Description of student learning difficulties in the acid-base material - Annisa Annisa; Fajriah Azra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Acid-base material is material that class XI IPA students study in the even semester. In this material, 81.38% of class XI IPA students at SMAN 16 Padang have yet to achieve the minimum criteria set. It indicates that students have learning difficulties. Learning difficulties are failures to attain learning goals characterized by low learning outcomes. This study aims to determine the percentage of students who experience learning difficulties for each indicator on acid-base material and determine the factors that cause learning difficulties experienced by students in terms of learning methods. Its research is a type of descriptive research. The sample for this research was students in class XI IPA 2 at SMAN 16 Padang in the 2022/2023 academic year, which consisted of 34 people. The research instrument was a diagnostic test with two-tier multiple-choice questionnaires and interviews. The data analysis used is descriptive, namely analyzing and then providing an understanding of the data in the form of numbers so that an overview can be given in an orderly, concise, and clear manner. The results of this study stated that students of SMAN 16 Padang had learning difficulties in acid-base material, with a percentage of 66.65% in the high category. The highest difficulty level is found in the first indicator (Analyzing the properties of the solution based on the acid-base theory according to Arrhenius, Bronsted-Lowry, and Lewis) of 72.88%. Ineffective learning methods cause learning difficulties experienced by students. Effective ways of learning are making study schedules and carrying them out, reading and taking notes, repeating subject matter, concentrating, and doing assignments.